Association of Sensory Processing and Eating Problems in Children with Autism Spectrum Disorders - Nadon, Geneviève (Hindawi Publishing Corporation, 2011)
“Selective” or “picky eating” is a frequent problem in children with autism spectrum disorders (ASD). Many of these children do not treat sensory input, particularly olfactory, auditory, visual, and tactile information in the same manner as their typically developing peers of the same age. The purpose of this paper was to examine the relationship between problems of sensory processing and the number of eating problems in children with ASD. Of 95 children with ASD, 3 to 10 years of age, 65 percent showed a definite difference and 21 percent a probable difference in sensory processing on the total score of the Short Sensory Profile. These results were significantly related to an increase in the number of eating problems measured by the Eating Profile. These results could not be explained by age, sex, mental retardation, attention deficit disorder, or hyperactivity. Timely interventions focusing on the sensory components of eating must now be developed.